KARAKTERISTIK DAN TIPOLOGI HAK-HAK KEPEMILIKAN DALAM PERIKANAN ARTISANAL - Apendi Arsyad; Tridoyo Kusumastanto; Rokhmin Dahuri; Asep Saefudin; Endriamo Soetarto (Buletin PSP, 2007)
The objective of the research is to explain about the rules of the traditional social institution, especially characteristic and typology of property rights on artisanal fishery management system at Abang island. Traditional institution pattern commonly has function for keeping continuity of coastal resources, so management that did by local fisherman society in coastal villages feel to keep well fishery resources and ecosystem, not disturbed by capture activity for example intake of rock, bombardment of fish and usage of potassium. Study case method that using is rural rapid appraisal (RRA) for coastal community. This research was done in Abang island village Galang subdistrict Batam city, try to identify and documentating several characteristic and typology of property rights on artisanal fishery at Abang island village. Based on result of research there are 8 fishing gears that dominant used by local fisherman, and other 2 modern fishing gears. Operation of trawl that has been prohibited based on Keppres No. 39/1980, still found in territorial water of Abang island. Eight of fishing gears that operated by fisherman, had fishing ground in around of territorial coastal water, farthermost catch fish by distance 3 or 4 miles from coast line. Generally fisherman here included small scale and traditional fisherman category, meant they become fisherman hereditarily, heritage of their parents, by using simply fishing gears, but they orientated to market, most of catch fish and prawn sold to merchant and tauke, called artisanal fisherman. For appliance catch selected like line, fisherman of Abang island catch fish collectively by using fish aggregating device cooperation result among fisherman. Most of fishing gears used by fisherman in this area are trap, line, longline, setnet, gillnet, fish cage, seine and fish-net. From a number of fishing gears divided again become some types, like net consist of beach seine, apollo net (trammelnet), trawl kara ( Lobster), stromateus net, gillnet and crab net.